2023
DOI: 10.1177/15593258231169584
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic and Antidepressant Potential of Methanolic Extract of Neurada procumbens Linn. in Mice

Abstract: Neurada procumbens Linn. possesses a wide range of phytochemical and bioactive entities such as flavonoids and polyphenols that decrease the oxidative stress and enhance synaptic plasticity, resulting in accelerated healing processes. Almost all parts of the plant have been used in the traditional system of medicine for various disorders including its use as an anticonvulsant, sexual tonic, and anti-rheumatic agent. This study is designed to evaluate the anxiolytic and antidepressant activities of the methanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Acute toxicity studies confirmed the wide safe margin for the use of OEE and demonstrated its low toxicity profile (Khalid et al, 2023). Carrageenan is a chemical that increases the local blood flow and capillary permeability, resulting in edema formation.…”
Section: Discussionmentioning
confidence: 87%
“…Acute toxicity studies confirmed the wide safe margin for the use of OEE and demonstrated its low toxicity profile (Khalid et al, 2023). Carrageenan is a chemical that increases the local blood flow and capillary permeability, resulting in edema formation.…”
Section: Discussionmentioning
confidence: 87%
“…The growing awareness of conventional pharmaceutical interventions' limitations and potential adverse effects has fueled interest in natural alternatives, such as plant-derived substances. 12 Plants with antidepressant and anxiolytic properties Many plants have been traditionally utilized and scientifically examined for their possible anxiolytic (anxiety-relieving) and antidepressant qualities. These plants frequently include chemicals that interact with neurotransmitter systems, especially those involving serotonin, dopamine, and gamma aminobutyric acid (GABA), all of which play important roles in mood regulation (Table 4).…”
Section: Human Trialsmentioning
confidence: 99%